Predicting the Prognosis of Gastric Cancer by Albumin/Globulin Ratio and the Prognostic Nutritional Index. (18th May 2020) - Zhang, Yan; Zhu, Jia-Yao; Zhou, Li-Na; Tang, Min; Chen, Min-Bin; Tao, Min
Abstract: Background: Albumin-to-globulin ratio (AGR) and the prognostic nutrition index (PNI) are used to assess the nutritional status and severity of disease for a cancer patient. However, the clinical significance of combining these two predictors in gastric cancer (GC) remains unclear. This study evaluated the prognostic value of pretreatment serum AGR and the PNI for GC. Methods: A total of 273 patients with GC, diagnosed between January 2010 and January 2014, were enrolled. The association of AGR, PNI with clinicopathological characters and prognosis were assessed by Cox regression and Kaplan–Meier methods. Results: Both low AGR group and low PNI group had poor overall survival (OS) and progression-free survival (PFS) (all p < 0.001), while patients with low AGR and PNI had the lowest OS rate. Multivariate analyses revealed that AGR (for OS HR = 0.657, 95%CI: 0.449–0.962, p = 0.031; for PFS HR = 0.684, 95%CI: 0.528–0.895, p = 0.035) was an independent prognostic factor for OS and PFS in patients with GC, and PNI was verified as a predictor for OS (HR = 0.782, 95%CI: 0.503 –0.997, p = 0.048). Conclusions: Low level of pretreatment AGR and PNI may be independent prognostic factors for patients with GC, and patients with both factors indicated the worst OS.